2004
DOI: 10.1111/j.0019-2805.2003.01795.x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Epstein–Barr virus by saliva from Sjogren's syndrome patients

Abstract: SUMMARYThe aim of this study was to examine the mechanism of Epstein±Barr virus (EBV) activation by soluble factors from the in¯amed salivary glands of patients with Sjogren's syndrome (SS). Saliva from SS patients was used to examine the regulation of EBV activation by an in¯amma-tory salivary microenvironment. Transient transfection of the EBV-negative salivary gland cell line (HSY) with BZLF1, a trans-activating EBV gene promoter-fusion construct (Zp-luc), was used in this study. The results showed that und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 51 publications
0
29
1
1
Order By: Relevance
“…3, 4). Our previous study demonstrated that Zp221 activity and BZLF1 transcription were induced by saliva from SS patients (63). TGFb1, which is expressed in SS salivary glands, induced Zp221 activity via the MAPK signaling pathway.…”
Section: Discussionmentioning
confidence: 92%
“…3, 4). Our previous study demonstrated that Zp221 activity and BZLF1 transcription were induced by saliva from SS patients (63). TGFb1, which is expressed in SS salivary glands, induced Zp221 activity via the MAPK signaling pathway.…”
Section: Discussionmentioning
confidence: 92%
“…Involvement of virus has been speculated for a long time, but despite the fact that several candidate viruses have been thought to play a role (e.g. EpsteineBarr virus [20,21] and coxsackieviruses [22]), evidence for their contribution in the initiation of the disease is still lacking.…”
Section: Role Of Type I Interferon (Ifna/b)mentioning
confidence: 99%
“…Therefore viral latency or intensive reactivation may have effects on the antibody production of B lymphocytes, and a contribution of EBV to various autoimmune diseases has been suggested (2,4,5,9,14,(17)(18)(19)(20)22,25,(30)(31)(32)34). For example, in multiple sclerosis (MS), and systemic lupus erythematosus (SLE), EBV infection is thought to be an important environmental trigger (4,22,34).…”
Section: Introductionmentioning
confidence: 99%